Serious gastric perforation after second stereotactic body radiotherapy for peripheral lung cancer that recurred after initial stereotactic body radiotherapy: a case report - Hotaka Nonaka; Hiroshi Onishi; Masatoki Ozaki; Kengo Kuriyama; Takafumi Komiyama; Ryo Saito (Journal of Medical Case Reports, 2017)
Abstract Background In recent reports, re-irradiation with stereotactic body radiotherapy for lung tumors in patients previously treated with thoracic radiation therapy resulted in several serious toxicities. Serious non-lung toxicities were observed mostly in patients with central tumors, but we experienced a case of fatal gastric perforation after a second stereotactic body radiotherapy in a patient with a peripheral lung tumor. Case presentation An 83-year-old Asian man was diagnosed with T2N0M0 lung cancer in the form of squamous cell carcinoma in the lower lobe of his left lung. He was treated with stereotactic body radiotherapy of 40 Gy in 4 fractions and the tumor decreased in size in partial response. The local tumor recurred 8 months after the first stereotactic body radiotherapy, and he was re-irradiated with a second stereotactic body radiotherapy of 50 Gy in 4 fractions. A Sengstaken–Blakemore tube was inserted below his diaphragm by laparoscopic surgery before the second stereotactic body radiotherapy in order to reduce the stomach dose by keeping his stomach apart from the tumor. Two months after the second stereotactic body radiotherapy, he developed fatal gastric perforation and gastropleural fistula penetrating his diaphragm. Conclusions To the best of our knowledge, this is the first report about a gastric perforation after stereotactic body radiotherapy for lung tumors and it warns of serious complication of stereotactic body radiotherapy in not only centrally located but also peripherally located tumors like in this case.